1995
DOI: 10.1002/elps.11501601143
|View full text |Cite
|
Sign up to set email alerts
|

Forensics on wild animals: Differentiation between otter and pheasant blood using electrophoretic methods

Abstract: Electrophoretic techniques were used to prove illegal hunting of a protected species as small amounts of dried blood stains could be clearly identified as of otter origin. Species differentiation between the otter (Lutra lutra) and pheasant (Phasianus colchicus) was based mainly on small differences in electrophoretic mobilities of the respective albumins and hemoglobins in one-dimensional separations. Additional differences in minor proteins of the two species were revealed by two-dimensional electrophoresis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…A comparison of the patterns was useful in locating the probable origin of some of the protein spots found in specimens collected from dead animals. For hemolytic samples the photometric estimation of the hemoglobin content [5] proved to be a useful marker for the presence of erythrocyte proteins. Only in hemolytic samples two spots in the apolipoprotein A-I region (with slightly lower molecular mass and higher PIS) were detected whose intensities seemed to correlate with the hemoglobin content.…”
Section: Comparison Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the patterns was useful in locating the probable origin of some of the protein spots found in specimens collected from dead animals. For hemolytic samples the photometric estimation of the hemoglobin content [5] proved to be a useful marker for the presence of erythrocyte proteins. Only in hemolytic samples two spots in the apolipoprotein A-I region (with slightly lower molecular mass and higher PIS) were detected whose intensities seemed to correlate with the hemoglobin content.…”
Section: Comparison Of Samplesmentioning
confidence: 99%
“…At the first glance, the most evident change is the position of albumin (SA); otter SA has a lower pZ and higher molecular mass [5] than HSA. Additional dissimilarities to human.…”
Section: Protein Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mid 1990's research included the use of albumins, hemoglobin's and hair keratins for species identification using electrophoresis (Miller et al, 1995, Folin andContiero, 1996). In 1995, Miller et al found differences in the electrophoretic mobility's of albumin and hemoglobin's using a 1-dimensional electrophoretic technique (Miller et al, 1995). They found differences between blood of the pheasant (Phasianus colchicus) and that of a protected species, otter (Lutra lutra) (Miller et al, 1995).…”
Section: Protein Forensicsmentioning
confidence: 99%
“…In 1995, Miller et al found differences in the electrophoretic mobility's of albumin and hemoglobin's using a 1-dimensional electrophoretic technique (Miller et al, 1995). They found differences between blood of the pheasant (Phasianus colchicus) and that of a protected species, otter (Lutra lutra) (Miller et al, 1995). A year later Folin and Contiero discovered mobility differences between non-human primates.…”
Section: Protein Forensicsmentioning
confidence: 99%